A Comparison of 2 Methods to Deter Fish Crows from Depredating Seabird Eggs. (3rd December 2020) - Forys, Elizabeth A.; Campo, Jo A.; Silva, Elisa; Douglass, Nancy J.
ABSTRACT: Fish crows ( Corvus ossifragus ) can be important seabird egg predators. In southwestern Florida, USA, crows were previously documented as causing the abandonment of black skimmer ( Rynchops niger ) colonies. While lethal crow control might be the most effective strategy, there are ethical and practical concerns about corvid control in an urban setting. Illness‐induced aversion to egg eating (conditioned taste aversion) is an alternative that has the potential for decreasing corvid depredation of seabird eggs. In addition, conditioned stimulus aversion using nonlethal shocks on corvids taking electrified eggs might also be effective. We tested conditioned taste aversion using quail eggs injected with carbachol (emetic eggs) at 3 black skimmer colonies during the 2016 breeding season. We tested conditioned stimulus aversion using electrified quail eggs at the same colonies during the 2017 breeding season. We compared the number of skimmer eggs in a colony depredated by crows before and after a 10‐day treatment. Both methods of treatment significantly decreased the number of skimmer eggs depredated by crows and were relatively inexpensive to conduct. In urban settings, electrified eggs are the safer option as many of the crows took the emetic eggs, but did not consume them while near the colony, potentially exposing non‐target species to a toxicant. © 2020 The Wildlife Society. Abstract : Fish crows ( Corvus ossifragus ) can be important seabird egg predators, but lethal control is not always possible or desired. We found that both conditioned taste aversion with emetic eggs and conditioned stimulus aversion using nonlethal shocks significantly reduced the number of eggs taken from black skimmers ( Rynchops niger ) nesting in southwestern Florida.